The marylebone drop ebook A novella. - Herron, Mick (Slough House, 2018)
The Marylebone Drop can now be found in the collection called Standing by the Wall: The Collected Slough House Novellas. A drop, in spook parlance, is the passing on of secret information. It’s also what happens just before you hit the ground. Old spooks carry the memory of tradecraft in their bones, and when Solomon Dortmund sees an envelope being passed from one pair of hands to another in a Marylebone café, he knows he’s witnessed more than an innocent encounter. But in relaying his suspicions to John Bachelor, who babysits retired spies like Solly for MI5, he sets in motion a train of events that will alter lives.